Durability of Nucleos(t)ide Analogues Treatment in Patients With Chronic Hepatitis B. Issue 32 (August 2015) - Lee, I-Cheng; Sun, Cheuk-Kay; Su, Chien-Wei; Wang, Yuan-Jen; Chang, Hung-Chuen; Huang, Hui-Chun; Lee, Kuei-Chuan; Huang, Yi-Shin; Perng, Chin-Lin; Liu, Yuh-Hwa; Chua, Chian-Sem; Lin, Yu-Min; et al.
<x xml:space="preserve">Abstract</x> Abstract Long-term nucleos(t)ide analogues (NUCs) treatment is usually required for patients with chronic hepatitis B (CHB). However, whether discontinuation of NUCs is possible in selected patients remains debated. The aim of this study was to assess the durability of NUCs and predictors of sustained response after cessation of NUCs. Ninety-three CHB patients (29 HBeAg-positive and 64 HBeAg-negative) from 2 medical centers in Taiwan with discontinuation of NUCs after a median of 3 years' treatment were retrospectively reviewed. Fifteen (51.7%) HBeAg-positive and 57 (89.1%) HBeAg-negative patients achieved APASL treatment endpoints. Virological relapse (VR) and clinical relapse (CR) were defined according to APASL guidelines. Achieving APASL endpoint was associated with longer median time to CR in HBeAg-positive patients, but not in HBeAg-negative cases. The cumulative 1-year VR and CR rates were 55.3% and 14.4% in HBeAg-positive patients, and 77.7% and 41.9% in HBeAg-negative patients, respectively. In HBeAg-negative patients, baseline HBV DNA >105 IU/mL was the only predictor of VR (hazard ratio [HR] = 2.277, P = 0.019) and CR (HR = 3.378, P = 0.014). HBsAg >200 IU/mL at the end of treatment (EOT) was associated with CR (HR = 3.573, P = 0.023) in patients developing VR. HBeAg-negative patients with low baseline viral loads and low HBsAg levels at EOT had minimal risk of CR after achieving APASL treatment endpoint (P = 0.016). The VR rate is high, but the risk of CR is low within 1 year with consolidation treatment after HBeAg seroconversion. Longer consolidation treatment to reduce the risk of VR should be considered in HBeAg-positive patients. As high risk of VR and CR, cessation of NUCs therapy could be considered only in selected HBeAg-negative patients.